Seleção de solos tropicais para produção de adobe: a utilização do ensaio de azul de metileno - Jaqueline Leite Ribeiro do Vale (2020)
The use of earth as a building material is one of the oldest techniques used by man. Even today, in various regions of the globe, earth materials, such as adobe, is used in the construction of housing, translating the identity, history, culture and way of life of various populations. Knowledge of the properties of the geotechnical materials involved in earth building techniques is essential and analyzing the activity of clays is a fundamental aspect in the characterization of the soil for the production of adobe. The present work aims to study the potential of the methylene blue adsorption test as an indicator of the degree of activity of the fine parts of tropical soils, seeking to develop a methodology for its use in the decision process on the type of soil to be used in historic and contemporary adobe constructions. Based on the analyzes carried out, the research results indicated that adobes produced with certain types of tropical soils, with grain sizes outside the standards indicated by adobe standards and references, presented good resistance to compression. Finally, through the results obtained through the analysis of the Multiple Linear Regression equations, it is concluded that the methylene adsorption test is an important tool to be adopted as a complementary test for choosing soil for the production of adobe with compression resistance appropriate according to standards and documents parameters.